Effect of supplementation of pelleted hazel (Corylus avellana) leaves on blood antioxidant activity, cellular immune response, and heart beat parameters in sheep - Wang, S.; Giller, Kenneth E.; Hillmann, E.; Marquardt, Svenja; Schwarm, A. (Oxford University Press, 2019)
Hazel leaves (Corylus avellana) fed to sheep resulted in decreased methane emissions without negatively affecting feed intake and were found to have antioxidant properties in vitro. The objective of this study was to evaluate effects of hazel leaves, rich in tannins, on blood antioxidant activity, cellular immune response, and heart beat parameters in sheep. Four experimental pellets were produced by mixing alfalfa and hazel leaves in different proportions, including alfalfa alone as a control, 30% and 60% of hazel leaves, the latter also with 3.8% polyethylene glycol (PEG). Six adult, nonpregnant, nonlactating female sheep (71 ± 5.7 kg of body weight) were allocated to 4 treatments in a 6 × 4 crossover design with four 18-d periods. The diet consisted of experimental pellets and ryegrass-dominated hay (ratio 80% to 20% in dry matter), resulting in hazel leaf proportions of approximately 0%, 25%, and 50% in the total diet. Blood samples were collected at the end of each period to determine plasma total phenol concentration and markers of oxidative status as well as peripheral blood mononuclear cells (PBMC) activation and proliferation response in vitro. Heart rate (HR) and HR variability parameters were measured for 2 consecutive days in each period, during different activities (i.e., eating pellets or hay, or lying). Treatments were compared with multiple comparisons and contrast analysis was used to test for linear and quadratic relations. Compared with control, feeding a high dosage of hazel leaves enhanced (P = 0.006) the plasma total antioxidant capacity, which linearly (P = 0.016) increased with increasing level of hazel leaves in the diet. The total phenol concentration and activities of the antioxidant enzymes superoxide dismutase, catalase, and glutathione reductase in the plasma were not different (P ≥ 0.23) among the treatments; however, the latter slightly increased linearly (P = 0.047) with increasing hazel leaves proportion. No differences were observed in the activation and proliferation of PBMC among treatments. The HR decreased linearly (P ≤ 0.009) during pellet eating and lying and the root mean square of successive differences of interbeat intervals (RMSSD) increased linearly (P = 0.037) when lying with increasing level of hazel leaves in the diet. In conclusion, our findings indicate that hazel leaves are a promising supplement to improve oxidative status with no effect on cellular immune response and cardiac stress level of sheep.